Irrigant flow characteristics in the root canal with internal root resorption: a computational fluid dynamics evaluation - Ciftcioglu, Elif; Yucel, Ozgun; Isik, Vasfiye; Keles, Ali; Kayahan, Mehmet Baybora (Springer, 2022)
Irrigation dynamics of syringe irrigation with different needle designs (side-vented, double side-vented, notched) and ultrasonic irrigation in the root canal with internal root resorption were evaluated using a computational fluid dynamics model. A micro-CT scanned mandibular premolar was used for modeling internal root resorption. The needles and the ultrasonic tip were positioned at 2, 4, and 5 mm from the working length. The insertion depth and the irrigation model were found influential on the shear stress and the irrigant extension. The extension of the irrigant increased toward 2-5 mm from the working length. Ultrasonic irrigation revealed the highest shear stress values regardless of the insertion depth. The shear stress distribution on the resorption cavity walls gradually increased when the needles were positioned coronally. The residence time of the irrigant in the canal was affected by the needle position relative to the internal root resorption cavity and the needle type.
Keywords: Computational fluid dynamics; Internal root resorption; Irrigation; Needles; Ultrasonic irrigation